Social Media, Spiral of Silence and Audience Reaction to Religious Media Contents: A Critical Analysis - Ifeanyi Martins NWOKEOCHA; Patrick Samuel EKPE; Promise Adaku OBI (International Journal of Education, Vocational and Social Science, 2026)
This research paper examines the impact of social media on public engagement with religious media content, the Spiral of Silence theory, and audience reactions to such content. Social media has transformed the way religious content is created, distributed, and consumed. However, the Spiral of Silence phenomenon holds that individuals are less likely to express views or opinions that they believe others will disagree with. The study explores how social media is affecting the willingness of individuals to discuss and engage with religious media contents and how individuals react to these contents. The paper highlights real-life examples of controversies in Nigerian religious social media and analyzes the potential risks and rewards of religious media content dissemination on social media. The study concludes that social media platforms have become key players in the dissemination of religious media contents and have created unique challenges and opportunities for religious communication. The Spiral of Silence theory is still applicable in the context of discussions about religious media contents on social media, and it has the potential to silence minority opinions and magnify the impact of dominant ones. Additionally, audiences' reactions to religious media contents on social media are diverse and complex, driven by a range of factors such as religious affiliation, personal beliefs, and broader societal trends. However, it is important to be mindful of the potential ethical and theological challenges that arise from producing and sharing religious media content on social media. Audiences' reactions to religious media contents are complex and can vary widely depending on several factors, including religious affiliation and societal trends. Finally, the study recommends ways to improve the dissemination of religious media content, increase user privacy and make algorithms more transparent, and prevent the spread of misinformation and hate speech. Future research should focus on further examining the impact of social media on the distribution and reception of religious media contents.